Proton induced DNA double strand breaks at the Bragg peak: Evidence of enhanced LET effect - Frame, Cara M.; Chen, Yu; Gagnon, Jonathan; Yuan, Y.; Ma, Tianjun; Dritschilo, Anatoly; Pang, Dalong (Frontiers in Oncology, 2022)
Purpose: To investigate DNA double strand breaks (DSBs) induced by therapeutic proton beams in plateau and Bragg peak to demonstrate DSB induction due to the higher LET in the Bragg peak. Materials and Methods: pUC19 plasmid DNA samples were irradiated to doses of 1000 and 3000 Gy on a Mevion S250i proton system with a monoenergetic, 110 MeV, proton beam at depths of 2 and 9.4 cm, corresponding to a position on the plateau and distal Bragg peak of the beam, respectively. The irradiated DNA samples were imaged by atomic force microscopy for visualization of individual DNA molecules, either broken or intact, and quantification of the DNA fragment length distributions for each of the irradiated samples. Percentage of the broken DNA and average number of DSBs per DNA molecule were obtained. Results: Compared to irradiation effects in the plateau region, DNA irradiated at the Bragg peak sustained more breakage at the same dose, yielding more short DNA fragments and higher numbers of DSB per DNA molecule. Conclusion: The higher LET of proton beams at the Bragg peak results in more densely distributed DNA DSBs, which supports an underlying mechanism for the increased cell killing by protons at the Bragg peak.